Transformation of Digital-Based Educational Human Resource Management : The impact of Online Attendance Systems and Digital Literacy on Teacher Performance and Discipline in Elementary Schools - Tut Wuri Handayani; Suparno Suparno; Aris Toening Winarni (International Journal of Social Science and Humanity, 2025)
This study investigates the influence of an online attendance system and digital literacy on teacher discipline and performance in elementary schools. A quantitative explanatory research approach was employed to provide empirical evidence regarding these relationships. The research population consisted of 170 elementary school teachers in Bojong District, Pekalongan Regency, who were selected using proportional stratified random sampling to ensure representativeness. Data were collected through a structured questionnaire using a 5-point Likert scale, and analyzed with Structural Equation Modeling (SEM) through the Partial Least Squares (PLS-SEM) approach using SmartPLS 4.0 software. The measurement model evaluation demonstrated strong reliability and validity across all constructs. Cronbach’s Alpha values ranged between 0.820 and 0.872, Composite Reliability between 0.881 and 0.911, and Average Variance Extracted (AVE) between 0.649 and 0.718. Discriminant validity was confirmed based on both the Fornell-Larcker Criterion and the Heterotrait-Monotrait Ratio (HTMT). The structural model showed good predictive relevance with a Goodness-of-Fit (GoF) value of 0.366, indicating a large effect. Hypothesis testing results supported all proposed relationships. Digital literacy was found to positively influence teacher performance, while the online attendance system significantly affected both teacher discipline and teacher performance. Furthermore, teacher discipline was proven to have a positive effect on teacher performance. Mediation testing revealed that teacher discipline acted as a significant partial mediator in the relationships between digital literacy, online attendance systems, and teacher performance. The findings provide empirical validation for the Task-Technology Fit Theory and the TPACK Framework in the context of educational human resource management. This study confirms that digital transformation, through strengthening digital literacy and online systems, represents an effective strategy to improve teacher professionalism and enhance academic quality in elementary schools.